(untitled) (International Journal of Engineering and Computer Science, 2017)
In industrial processes, unstable system produces undesirable peak overshoot. So, PID controller with compensator and set point filter is designed using direct synthesis method. The set point filter reduces the peak overshoot. PID controller with compensator improves the overall response of the system. In this method, the characteristics equation of the system with PID controller and a compensator is compared with a desired characteristics equation. A single tuning parameter is used to find controller parameters, compensator and set point filter.